Assembly and transport of filovirus nucleocapsids - Dolnik, Olga; Becker, Stephan (PLoS pathogens, 2022)
Filovirus-infected cells are characterized by typical cytoplasmic inclusion bodies (IBs) located in the perinuclear region. The formation of these IBs is induced mainly by the accumulation of the filoviral nucleoprotein NP, which recruits the other nucleocapsid proteins, the polymerase co-factor VP35, the polymerase L, the transcription factor VP30 and VP24 via direct or indirect protein–protein interactions. Replication of the negative-strand RNA genomes by the viral polymerase L and VP35 occurs in the IBs, resulting in the synthesis of positive-strand genomes, which are encapsidated by NP, thus forming ribonucleoprotein complexes (antigenomic RNPs). These newly formed antigenomic RNPs in turn serve as templates for the synthesis of negative-strand RNA genomes that are also encapsidated by NP (genomic RNPs). Still in the IBs, genomic RNPs mature into tightly packed transport-competent nucleocapsids (NCs) by the recruitment of the viral protein VP24. NCs are tightly coiled left-handed helices whose structure is mainly determined by the multimerization of NP at its N-terminus, and these helices form the inner layer of the NCs. The RNA genome is fixed by 2 lobes of the NP N-terminus and is thus guided by individual NP molecules along the turns of the helix. Direct interaction of the NP C-terminus with the VP35 and VP24 molecules forms the outer layer of the NCs. Once formed, NCs that are located at the border of the IBs recruit actin polymerization machinery to one of their ends to drive their transport to budding sites for their envelopment and final release. Here, we review the current knowledge on the structure, assembly, and transport of filovirus NCs.